Structural and Textural Properties of Perchlorated and Persulphated Mixed (Hydr)Oxides of Zirconium and Titanium - Gamal M.S. El Shafei; Afaf A. Zahran (Adsorption Science & Technology)
Perchlorated and persulphated mixed hydroxides of zirconium and titanium were prepared by coprecipitation and impregnation in aqueous HClO 4 or (NH 4 ) 2 S 2 O 8 solutions of 0.05, 0.10, 0.20 and 0.40 M concentrations. An alternate sequence of impregnation followed by calcination or vice versa was conducted and the samples obtained studied using XRD, FT-IR, pyridine titration and low-temperature (–196°C) nitrogen adsorption methods. XRD indicated that the presence of titanium stabilized the tetragonal modification of zirconia and almost completely prevented the usual tetragonal → monoclinic transformation upon calcination at 650°C. Both S 2 O 8 2– and ClO 4 − anions at their lowest concentration level (0.05 M) partially retarded the crystallization which occurred upon calcination at 650°C in their absence. However, the two anions showed different effects. Whereas the perchlorate anion prevented the formation of a crystalline titania phase (anatase) to a greater extent than that of crystalline zirconia, the persulphate anion showed the opposite effect. Complete inhibition was observed with both anions at a concentration of 0.4 M. This effect was attributed to adsorption of the anions on the hydroxy species of zirconium and titanium formed initially, as demonstrated by IR spectroscopy which showed that the anions were of lower symmetry, viz. C 2v , due to their bonding to the hydroxy species. Calcination at 650°C caused the material formed initially to lose virtually all its initial high surface area because of crystallization. The prevention of crystallization by added anions was reflected in the retention of a relatively high surface area even after calcination at 650°C. The recorded difference in the interactions of the anions with the hydroxy species formed initially was also reflected in the texture of the anion-modified solids. The protecting influence of the ClO 4 − anion increased with its increasing concentration in the system, whereas the corresponding effect with the S 2 O 8 2– anion increased up to 0.10 M concentration and then decreased at higher concentrations.